A Business Perspective on Internet of Things (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Sensors are rapidly being integrated everywhere, in every aspect of our lives, ranging from home automation to wearable sensors for pervasive healthcare management. We hear ubiquitously for ubiquitous devices. In recent years, increasingly we are listening and talking about phrases like “Internet of Things”, “M2M”, “Context awareness”, “Web of Things”, which announce the new era to come, where we will be surrounded with smart devices, which communicate with each other to easer and beautify our lives. This article reports on our findings about the business perspective on internet of things. It involves literature review on the internet of things world and its impact in the business domain.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.